Gestión de seguridad y salud ocupacional en la Municipalidad Distrital de San Juan Bautista 2023 - Moncada Garcia, Christhiam Jhordam (2024)
The purpose of the study was to make the link between security administration and occupational protection in the District Municipality of San Juan Bautista, 2023. A descriptive-correlational investigation was carried out, with a non experimental design, in which a sample of 152 employees and a questionnaire was applied to collect information. The results indicate that safety management is considered regular (30%) and occupational health is rated equally (30%). Furthermore, a significant correlation was determined between both, demonstrated by a coefficient of 0.830, which is in the range of strong positive correlation, with a bilateral significance of 0.000. Likewise, a relationship is established between the work environment dimension (r=0.702; p = 0.000), and the OHS training dimension (r= 0.687; p = 0.000), for the safety signaling dimension (r= 0.699). ; p = 0.000), the cleaning/maintenance dimension (r= 0.587; p = 0.000), for the common areas (r= 0.674; p = 0.000), finally for the toilet services dimension (r= 0.660; p = 0.000). ) all of them are positively and significantly related to occupational health in the municipality.